ANALISIS PENGEMBANGAN PEGAWAI MELALUI PENDIDIKAN DAN PELATIHAN DI DINAS SOSIAL KOTA YOGYAKARTA - Andamari, Ika Mustika; Dwimawanti, Ida Hayu (Journal of Public Policy and Management Review, 2018)
Employee development is an activity that is intentionally carried out to improve employee competencies both ability and behavior, one of the forms is through education and training. One of the reasons Social Department of Yogyakarta City has to do employee development is due to qualifications. Some employees do not meet the qualifications of their positions. The problem of employee development through education and training at at Social Department of Yogyakarta City is that there are still employees who have not shown significant improvement in skills or behavioral changes after attending education and training. This study aims to analyze employee development through education and training at Social Department of Yogyakarta City, as well as analyzing the factors that become drivers and inhibitors. The stages of employee development consist of identification of needs, targeting, program design selection, and monitoring and evaluation. This research uses descriptive qualitative method. The results showed that the education and training carried out at Social Department of Yogyakarta City was in accordance with the needs of Social Department of Yogyakarta City, but the education and training held had not been able to achieve the target due to the lack of motivation of some employees and also monitoring of employees who did after attending education and training. Factors that support the implementation of education and training in at Social Department of Yogyakarta City are the vision and mission, the nature and types of activities, and government policies, while the hindering factors are the lack of availability of technology in the form of computers and laptops, as well as the lack of awareness of some employees to develop themselves.